The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.pscychresns.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Brain gray matter phenotypes across the psychosis dimension

Abstract: This study sought to examine whole brain and regional gray matter (GM) phenotypes across the schizophrenia (SZ)–bipolar disorder psychosis dimension using voxel-based morphometry (VBM 8.0 with DARTEL segmentation/normalization) and semi-automated regional parcellation, FreeSurfer (FS 4.3.1/64 bit). 3T T1 MPRAGE images were acquired from 19 volunteers with schizophrenia (SZ), 16 with schizoaffective disorder (SAD), 17 with psychotic bipolar I disorder (BD-P) and 10 healthy controls (HC). Contrasted with HC, SZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 109 publications
13
35
0
Order By: Relevance
“…In the first of these 24, which was carried out on small numbers of subjects (<20 in each group), the patients with schizophrenia and schizoaffective disorder, but not the patients with bipolar disorder showed volume reductions compared to healthy controls; the changes also appeared to be considerably more extensive in the patients with schizophrenia than the patients with schizoaffective disorder. The second, much larger, study 25 had findings similar to ours: 146 patients with schizophrenia and 90 patients with schizoaffective disorder showed gray matter volume reductions compared to 200 healthy controls in numerous and overlapping areas, whereas changes in 115 patients with psychotic bipolar disorder were restricted to a single cluster in the frontotemporal cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first of these 24, which was carried out on small numbers of subjects (<20 in each group), the patients with schizophrenia and schizoaffective disorder, but not the patients with bipolar disorder showed volume reductions compared to healthy controls; the changes also appeared to be considerably more extensive in the patients with schizophrenia than the patients with schizoaffective disorder. The second, much larger, study 25 had findings similar to ours: 146 patients with schizophrenia and 90 patients with schizoaffective disorder showed gray matter volume reductions compared to 200 healthy controls in numerous and overlapping areas, whereas changes in 115 patients with psychotic bipolar disorder were restricted to a single cluster in the frontotemporal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In the first of these, Ivleva et al. 24 examined 19 patients with schizophrenia, 16 with schizoaffective disorder, and 17 with bipolar psychotic disorder, as well as 10 healthy controls. They found decreased gray matter volume in the patients with schizophrenia, and there were similar, albeit less extensive, changes in the patients with schizoaffective disorder; however, the patients with bipolar disorder did not differ from the controls.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, SCZ and BD were compared between each other and to HC, as well as to schizoaffective disorder (SAD) patients in Ivleva et al (2012Ivleva et al ( , 2013; Amann et al (2016), and to their firstdegree relatives in Ivleva et al (2013). It is worth noticing that Yüksel et al (2012) included SAD patients in the SCZ group.…”
mentioning
confidence: 99%
“…Some studies reported lower GM volume in SCZ than in BD in the temporal lobe, mainly in insula and temporal gyri (McDonald et al 2005;Ivleva et al 2013;Nenadic et al 2015a, b). A few works also reported occipito-parietal deficits associated with SCZ, mainly in lingual gyrus and precuneus (McDonald et al 2005;Ivleva et al 2012), as well as deficits in cingulum (Ivleva et al 2013) and subgenual cortex (Yuksel et al 2012). The widespread GM deficits emerged from these studies may be related to the lower WM metabolism in frontal, parietal and temporal areas characterising SCZ in comparison with BD (Altamura et al 2013).…”
mentioning
confidence: 99%
“…A shared aetiology between schizophrenia and bipolar disorder with psychosis is supported by findings from genetic (Lee et al), neuropsychological (Hill et al, 2013), phenomenological , structural (Ivleva et al, 2012) and functional neuroimaging studies (Li et al, 2017). It is important to see if any shared aetiology is reflected in similar, or related patterns of pathophysiology in adolescent-onset cases, where neurodevelopmental processes are likely to operate.…”
Section: Introductionmentioning
confidence: 98%